Relações corporais, composição centensimal e rendimento de filé do mandi (Pimelodus britskii), do Reservatório Salto Santiago - Rio Iguaçu - Almeida, Mara Cristina de (2010)
The mandi-pintado (Pimelodus britskii) a endemic species from Iguaçu River basin seems to have high potential for commercial exploitation. Thus, the aim of this study was to evaluate the potential for commercial exploitation of the mandi (Pimelodus britskii) through analysis of body proportions, centesimal composition and fillet yield of fishes collected in the Salto Santiago reservoir. Catches occurred in May and July 2009 by longlines and gillnets distributed throughout the reservoir. After capture fishes were weighed, measured and sexed. They were divided into size classes (fish <150g, 150-300g fish and fish> 300g) Morphometric data (total length, standard length, head height, head length, trunk height and width), fillet yield, abdominal muscle, cleaned trunk without skin and centesimal composition were obtained. Differences between size classes were tested by one-factor ANOVA. Significant differences were found for height(16,48-26,29%) and width of the trunk(10,55-15,20%), length(27,5-38,06%) and width of the head(16,45-20,56%), fillet yield(37,26%), abdominal muscle(7,28%), cleaned trunk(50,09%), moisture(77,88%), lipids(13,33%) and ash(1%) among size classes. Overall Pimelodus britskii presented morphometric relationships, fillet yield and centesimal composition at levels comparable to other commercially exploited species, demonstrating that this species has high potential for commercial exploitation, either through fishing or farming